TANGGUNG JAWAB PELAKSANAAN PENAGIHAN PIUTANG MILIK X CREDIT COMPANIES OLEH LEMBAGA JASA PENAGIHAN - Ricky Fajar Adiputra; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2019)
Financing Company is a business entity that carries out credit activities for goods or services for the productive and consumer interests. The problems encountered in this study are the constraints of the Financing Company when carrying out executions with fiduciary certificates, still having difficulty in collecting receivables from consumers. The next problem is responsibility for carrying out the work by the debt collector when carrying out fiduciary executions. This research is normative juridical, by approaching the case and the applicable laws and regulations. If Consumer in carrying out the obligation does not make payment, the Financing Company will execute the vehicle based on the Fiduciary Certificate, by first giving a warning to Consumer to immediately carry out its obligations, which is done because execution of the fiduciary guarantee is permissible by law based on Article 29 of Law No. 42 of 1999 concerning Fiduciary Guarantees. While in the case of cooperation between Financing Company and the Company that houses the Debt Collector, it is permissible based on Otoritas Jasa Keuangan Regulation Nb. 35 / POJK.05 / 2018. Regarding the legal responsibility itself is in the Financing Company. So it can be said that the execution of fiduciary guarantees by fiduciary recipients is permissible, and the finance company is responsible for the execution of executions, including those carried out by the Debt Collector. Therefore it is necessary to make procedures in accordance with the regulations so that the execution can be carried out properly and the Financing Company avoid legal responsibilities.